Treatment of cutaneous leishmaniasis with radiofrequency microneedling - S. Saeed, Mohammed; K. Al-Sudany, Nameer; Naif, Alaa; S. Al Chalabi, Qasim (Journal of Pakistan Association of Dermatologists, 2023)
Objectives: To assess the efficacy of radiofrequency microneedling in the treatment of cutaneous leishmaniasis particularly in preventing or at least minimizing the potential scarring Patients and methods: This is an open interventional therapeutic trial and was conducted in a private dermatology clinic in Missan province, Iraq between the period from January 2019 to December 2021. Sixty patients diagnosed with cutaneous leishmaniasis participated in this study. A detailed history and examination were done on every patient. We used a radiofrequency microneedling machine (NBW-FR200)© to treat lesions of CL. The depth of microneedles used in this study ranged from 2 to 3 mm according to the area treated and the degree of lesional induration. The interval between sessions was one week. The status of each lesion was documented every week including size and degree of erythema and of induration. Results: Only 54 patients completed the trial period, their age was 15.4 ± 13.3 years. The male to female ratio was 0.8:1. The duration of lesions ranged from 25 days to 5 months. A solitary lesion was encountered in 23 patients, the total number of treated lesions was 125 and the upper limbs were the most commonly affected area. The size of lesions ranged from 0.5 to 6 cm in diameter with a mean ± SD of 2.46 ± 1.17 cm. and ulcerative type was seen in 75 (60%) lesions. Two to six therapeutic sessions were done for all patients and the cure rate was 88.8%. Most patients encounter minor side effects after therapeutic sessions. All treated patients were followed up every month for 6 months. No recurrence has been detected in all cases. Conclusion: Radiofrequency microneedling has a high cure rate for cutaneous leishmaniasis with minimal side effects.